The Promise and Peril of Environmental Justice - Foreman, Christopher H. (Brookings Institution Press, 2011)
Are we environmentally victimizing, perhaps even poisoning, our minority and low-income citizens? Proponents of ""environmental justice"" assert that environmental decisionmaking pays insufficient heed to the interests of those citizens, disproportionately burdens their neighborhoods with hazardous toxins, and perpetuates an insidious ""environmental racism."" In the first book-length critique of environmental justice advocacy, Christopher Foreman argues that it has cleared significant political hurdles but displays substantial limitations and drawbacks. Activism has yielded a presidential exe.